Pemberdayaan Komunitas Herbal Medicine Class di Tangerang Selatan dalam Meningkatkan Kesehatan Keluarga - Adi, Lukas Tersono; Shaluhiyah, Zahroh; Widjanarko, Bagoes (UI Scholars Hub, 2023)
Background: More than 2 years since the COVID-19 disaster has passed, it has left homework for all nations in the world, including the Indonesian government, which has made every effort to control the spread of the disease. At that time community-based health efforts in Indonesia were 63.6% active, there was potential that had not been explored optimally in protecting public health as a whole. Purpose: Observing community participation in health empowerment and processing independently within the family. Method: Using qualitative methods in the form of case studies using data taken from secondary data sources from Herbal Medicine Class community manager,observations, interviews with 12 informants. Data analysis was carried out using content analysis techniques in which the researcher interpreted the research according to the research problem. Results: The community provides space for community participation for targets that have not been reached through a technological approach, local wisdom, and a conducive atmosphere in society, in fact helping the healing process, capacity building, health protection, including role models as facilitators and companions. The success of community empowerment lies in the commitment and empowerment model. Conclusion: Community empowerment can achieve health sovereignty by prioritizing the family, creating a conducive atmosphere, always respecting the quality of life and local wisdom and role models.